Precise predictions for (nonstandard) Wγ+ jet production - Campanario Pallás, Francisco; Englert, Christoph; Spannowsky, M. (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
We report on a detailed investigation of the next-to-leading-order QCD corrections to Wγ+jet production at the Tevatron and the LHC using a fully flexible parton-level Monte Carlo program. We include the full leptonic decay of the W, taking into account all off-shell and finite width effects, as well as nonstandard WWγ couplings. We find particularly sizable corrections for the currently allowed parameter range of anomalous couplings imposed by LEP data. In total, the next-to-leading-order differential distributions reveal a substantial phase-space dependence of the corrections, leaving considerable sensitivity to anomalous couplings beyond scale uncertainty at large momentum transfers in the anomalous vertex.
Gesehen am 27.06.2022